Update on the Relationship Between Depression and Neuroendocrine Metabolism - Qiu, Wenxin; Cai, Xiaodan; Zheng, Chenhui; Qiu, Shumin; Ke, Hanyang; Huang, Yinqiong (Frontiers in Neuroscience, 2021)
Through the past decade of research, the correlation between depression and metabolic diseases has been noticed. More and more studies have confirmed that depression is comorbid with a variety of metabolic diseases, such as obesity, diabetes, metabolic syndrome (MS) and so on. Studies showed that both depression and metabolic diseases exist chronic inflammatory state, and the level of inflammatory factors is significantly related to their severity. In addition, they also involve endocrine, immune and other systems. At present, the clinical treatment of depression is mainly drug and non-drug combination treatment, but the effect is limited. Therefore, exploring the co-disease mechanism of depression and metabolic diseases is helpful to find a new way for depression therapy. Herein, focusing on the relationship between depression and metabolic diseases, this manuscript aims to provide an overview of the co-disease mechanism of depression and metabolic diseases in chronic inflammation, endocrine and immunity.